2005
DOI: 10.1111/j.1399-3062.2005.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose amphotericin for prevention of serious fungal infection following liver transplantation

Abstract: The use of amphotericin B, liposomal or non-liposomal preparations at low doses, for prophylaxis of IFI in high-risk LT patients, is associated with a low incidence of serious fungal infection. In this randomised study, low-dose amBisome prophylaxis was associated with an increased likelihood of successful discharge from the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The pathogens causing IFI in our study were consistent with previous reports(2, 58, 18, 19). Yeasts ( Candida spp., Cryptococcus neoformans and Saccharomyces cerevisiae ) accounted for 91% (21/23) of disease-causing isolates.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The pathogens causing IFI in our study were consistent with previous reports(2, 58, 18, 19). Yeasts ( Candida spp., Cryptococcus neoformans and Saccharomyces cerevisiae ) accounted for 91% (21/23) of disease-causing isolates.…”
Section: Discussionsupporting
confidence: 93%
“…The observation that IFIs in low-risk patients were sufficiently uncommon as to not require prophylaxis (Supplemental Table 1)(4, 8, 16) supports AST and IDSA recommendations for targeted prophylaxis in liver transplantation(911). Specific definitions of “high-risk” liver transplant recipients differ dramatically across studies; nevertheless, our data clearly verify that antifungal prophylaxis in this population is effective (Supplemental Table 2)(58, 1719). In particular, our IFI rate of 6% among high-risk patients compares favorably to rates of 15–35% in studies of high-risk patients not receiving prophylaxis(6, 20).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The emergence of molds as an important pathogen in recipients of liver transplantation and the growing presence of other mycelial molds as pathogens were the most important factors. Other recent studies have examined the effectiveness of ABLC, showing a lower incidence of severe fungal infections as well as increased likelihood of successful discharge from the intensive care unit in liver transplant recipients who receive ABLC as prophylaxis 26–28…”
Section: Discussionmentioning
confidence: 99%
“…However, one trial demonstrated that prophylaxis with aerosolized ABLC and fluconazole in HSCT recipients was well-tolerated, with 1 of 40 patients developing a breakthrough IFI while receiving study medication (mean duration of treatment was 59 days post HSCT) [87]. In SOT patients, prophylactic regimens with lipid formulations appear to be associated with a low incidence of IFI although further data are required [88][89][90][91]. In neutropenic patients with hematologic malignancies or solid tumors, prophylactic inhalation of aerosolized amphotericin B also demonstrated no benefit [92].…”
Section: Amphotericin Bmentioning
confidence: 97%